Dissociation of the inhibitory effects of 2-deoxy-D-glucose on Vero cell growth and the replication of herpes simplex virus. - Spivack, J G (1982)
Vero cells treated for 24 h with a concentration of 2-deoxy-D-glucose (2dGlc) that inhibited the production of infectious herpes simplex virus type 1 grew at the same rate as untreated cells. Longer exposures to 2dGlc inhibited the growth of Vero cells in a dose-dependent manner, but without any loss of viability, and could be reversed by replating the cells in the absence of drug. To exhibit antiviral activity, 2dGlc had to be present during the replication cycle of herpes simplex virus type 1. Treatment of Vero cells, even with a cytotoxic dose of 2dGlc, was without effect on the yield of infectious virus, provided the drug was removed before infection. Thus the antiviral effects of 2dGlc were not the result of, and appeared to be independent of, persistent host cell toxicity.